Overview of non-contributory social protection programmes in South Asia from a child and equity perspective - Pedro Lara de Arruda; Yannick Markhof; Isabela Franciscon; Wesley de Jesus Silva; Charlotte Bilo (International Policy Centre for Inclusive Growth (IPC-IG), 2020)
This Research Report summarises an analysis of 51 non-contributory social protection programmes led by central government in the eight countries of South Asia. The sample manages to capture the flagship initiatives of national systems, providing a broad overview of current relevant social protection systems in the region.
Keywords: 330; social protection systems; South Asia; targeting mechanisms; cash transfers